Downstream Critical Process Parameters for COVID-19 mRNA LNP Vaccine Production - Aliyansah, Pradip Iramdhan; Kalyubi, Adelia Talita Oriana Athoulloh; Widiyanto, Azura Luna; E, Ervin; Loavenia, Michelle; Putri, Stevanie; Yuan, Tissa; Hartrianti, Pietradewi (Universitas Bio Scientia Internasional Indonesia, 2024)
The COVID-19 pandemic, triggered by the SARS-CoV-2 virus, has led to global efforts to mitigate its effects, with mRNA vaccines playing a crucial role. These vaccines use the virus's genetic sequence to prompt an immune response without introducing the live pathogen, showcasing substantial efficacy in protective immunity. The production of mRNA vaccines involves complex stages, including critical downstream processes of purification and formulation, vital for ensuring the vaccine's purity, potency, and safety. The structural components of mRNA vaccines, such as the Open Reading Frame (ORF), untranslated regions (UTRs), cap structure, and poly(A) tail, along with the delivery system using lipid nanoparticles (LNPs), are essential for their functionality and efficacy. Optimization of these elements is crucial for enhancing vaccine performance. Conventional, self-amplifying, and trans-amplifying mRNA vaccines represent the different strategies employed to target COVID-19 effectively. Each type utilizes structural and delivery innovations to stimulate a robust immune response. The review underscores the significance of precise control in the manufacturing process, highlighting its role in global health security and the advancement of vaccine technology. By understanding and optimizing critical process parameters (CPPs) in the downstream manufacturing process, the pharmaceutical industry can achieve the highest standards in vaccine production, significantly contributing to the fight against the pandemic and future vaccine development, ensuring a swift, effective response to global health crises. This review paper focuses on the downstream stages of mRNA vaccine production, comparing studies on CPP to emphasize the importance of stringent control measures for vaccine quality, safety, and efficiency.